Pengaruh Green Trust, Perceived Behavioral Control, and Green Marketing terhadap Green Purchase Intention Gen Z di Banjarmasin pada Lunch Box Tupperware Ramah Lingkungan - Nita Damayanti; Raden Roro Yulianti Prihatiningrum (Journal of Management and Business, 2025)
This research was conducted to (1) analyze the influence of green trust on green purchase intention of Tupperware lunch boxes in Banjarmasin, (2) analyze the influence of perceived behavioral control on green purchase intention of Tupperware lunch boxes in Banjarmasin. (3) analyze the influence of green marketing on the green purchase intention of Tupperware lunch boxes in Banjarmasin. This type of research is a quantitative approach. The population in this research is Gen Z in Banjarmasin. The research respondents ware 105 using a purposive samp;ing technique that is gen z in Banjarmasin who know Tupperware lunch box products and were aged 17-24 years. Data obtained using multiple linear regression analysis. The results of this study prove that perceived behavioral control has a positive and significant effect on green purchase intention, the greater the perceived behavioral control, the stronger the consumer's intention to purchase environmentally friendly Tupperware lunch box products. In addition, this study also proves that green marketing has a positive and significant effect on green purchase intention, meaning that green marketing has an important role. Other findings show that there is no effect of green trust on green purchase intention, which shows that there is a decrease in consumer confidence in environmentally friendly Tupperware lunch box products.